Functional outcome of anterior cruciate ligament reconstruction using bone-patellar tendon-bone graft: a descriptive observational study from Telangana - Singh, K. Jaya Krishna; Prasad, V. K. V.; Singh, T. Ashita; Takalkar, Anant A. (International Journal of Research in Orthopaedics, 2021)
Background: The knee joint is the most commonly injured of all joints and the anterior cruciate ligament is the most commonly injured ligament. The bone-patellar tendon-bone (BPTB) autograft is the most commonly used autograft for reconstruction. The bone-patellar tendon-bone autograft has been widely accepted as the gold standard for ACL reconstruction with a high success rate. Objectives of the study were to study the functional outcome of ACL reconstruction using BPTB graft. Methods: The present descriptive observational study was carried out at department of orthopedics, Mediciti institute of medical sciences, Hyderabad involving 30 patients of ACL tear by simple random sampling method. Patients were then evaluated by both subjectively and objectively. They were evaluated by using Lysholm and Gilquist knee scoring scale. Data was analyzed by using SPSS 24.0 version IBM USA. Results: Majority of the patients i.e., 13 (43.3%) were from 26-35 years age group with right sided involvement in 60%. The result was found to be good in 16 i.e., 53.3%, excellent in 10 i.e., 33.3% and fair in 4 i.e., 13.3% patients. Prevalence of complications was reported as 23.3% in our study. Conclusions: Our study of ACL repair using BPTP gives good to excellent results within a span of one year.